PENDIDIKAN KETERAMPILAN HIDUP (LIFE SKILL): PROGRAM PELATIHAN PENGELASAN LISTRIK BAGI TENAGA PRODUKTIF PENGANGGURAN DI KABUPATEN BANGKALAN - Hidayat, Rachmad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
Electric welding training held for 20 days, where participants will be given motivation to work and welding techniques. Activities carried out by focusing the skills, so 70% of the activity, an internship, 20% is the deepening of the theory of welding, and 10% is enlightenment activities to increase motivation.  Instructors part  of the permanent  faculty Trunojoyo  University, others are practitioners in the field of electric welding. The result of this activity are: (1) to produce 40 skilled people who can perform the electric welding, which already has a local certified welding, electrical (2) to produce 40 skilled people who can compete with other workers (3) produces 40 skilled people who can be channeled directly to work as an electric welding workers